HUBUNGAN OBESITAS DAN POLA MAKAN TERHADAP HIPERTENSI PADA PASIEN DI RSUD PARIAMAN - SALMAN; DORA, MECHI SILVIA; ZAYANI, NOFRI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2023)
The current trend of society with modern lifestyles is to change food consumption patterns, namely those high in salt and fat. Medical record data at the Kota Pariaman Regional Hospital shows that hypertension ranks second among the 10 most common diseases, with 652 cases. The aim of the research was to determine the relationship between obesity and diet and hypertension levels in the Pariaman Hospital's internal medicine clinic. Type of quantitative research with a cross-sectional approach. Sampling was carried out using a total sampling technique with a sample size of 56 respondents. The data collection tool used was a questionnaire. Data analysis with correlation analysis using SPSS at α = 5%. The results of the study showed that patients in the internal medicine clinic at Kota Pariaman Regional Hospital were categorized as not obese (67.9%), had poor diet (57.1%), and had hypertension (53.6%). Based on correlation analysis, there is a relationship between obesity and the level of hypertension and diet and the level of hypertension in the internal medicine clinic at Pariaman Hospital (p-value = 0.000 < α = 0.05). In conclusion, there is a relationship between obesity and diet and the incidence of hypertension in patients in the internal medicine clinic at Kota Pariaman Regional Hospital.